TINGKAT PERKEMBANGAN WILAYAH KABUPATEN PADANG PARIAMAN TAHUN 2015 DAN 2020 DI TINJAU DARI FASILITAS SOSIAL - Asalat, Abiyyu Faruq; Ahyuni, Ahyuni (JURNAL BUANA, 2026)
This research aims to (1) analyze the distribution and utilization of social facilities in Padang Pariaman Regency, (2) analyze the accessibility of social facilities in serving the community in Padang Pariaman Regency. The sampling technique used in this research employed documentation methods and secondary data obtained from various institutions such as the Central Bureau of Statistics (BPS), Regional Development Planning Agency (Bappeda), research reports, and relevant article publications. Based on the research findings, the distribution of education facilities in Padang Pariaman Regency showed an increase from 2015 to 2020. However, there was a decrease in the number of auxiliary health centers (puskesmas pembantu). The distribution pattern revealed that junior high schools (SMP), hospitals (rumah sakit), and health centers (puskesmas) were scattered. On the other hand, high schools (SMA) and sub-district health centers (pustu) exhibited a random distribution pattern. Elementary schools (SD) were found to be clustered. Regarding the accessibility of education and health social facilities in Padang Pariaman Regency, the results indicated that the accessibility percentages were as follows: 35.81% for elementary schools (SD), 64.02% for junior high schools (SMP), 72.2% for high schools (SMA), 27.35% for hospitals (RS), 91.07% for health centers (puskesmas), and 46.82% for sub-district health centers (pustu).